Penerapan Sistem Pemantau dan Pengaturan Cerdas untuk Unsur Hara pada Sistem Hidroponik NFT - Adinda Nurul Huda Manurung (Jurnal Pertanian Presisi (Journal of Precision Agriculture), 2018)
Smart systems are the application of a system that mirrors the method of processing the human brain. Smart systems are automatically computerized; the purpose of helping a work designed by humans requires monitoring continuous with high accuracy. The purpose of the research was to implement a smart system that is monitoring nutrients in hydroponic systems. Hydroponic is a method of planting a plant by using water as a substitute for soil media that requires care and maintenance of plants to grow properly. Hydroponic requires a number of nutrients. Problems into nutrition, apart from being consumed by plants found in hydroponic systems, because the content of nutrient levels to reduce, nutrients experience a reduction in nutrient content caused by changes in temperature and humidity in nutrient solutions in nutrient solution storage containers. This study was tried a smart system to monitor nutrient levels in hydroponic systems using nutrient sensors, temperature, and humidity. Nutrition monitoring requires an analytical method in measuring nutrient levels to determine Electrical Conductivity (EC) in hydroponic plants. Based on the EC results obtained, if measured below the specified limit, it will increase the nutrient solution. Whereas if it is above the EC value limit, it will add water. Determination of the boundary will give the effect of the growth of hydroponic plants that are good and stable and the concentration of nutrient levels and temperature on changes effectively and efficiently. Keywords : Smart control, Hydroponic Media, Nutrients, Electrical Conductivity (EC)